2011
DOI: 10.1161/atvbaha.111.235184
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Proteoglycans Mediate the Angiogenic Activity of the Vascular Endothelial Growth Factor Receptor-2 Agonist Gremlin

Abstract: Objective-Heparan sulfate proteoglycans (HSPGs) modulate the interaction of proangiogenic heparin-binding vascular endothelial growth factors (VEGFs) with signaling VEGF receptor-2 (VEGFR2) and neuropilin coreceptors in endothelial cells (ECs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 59 publications
3
85
0
Order By: Relevance
“…These data also suggest that rhGrem1 is not binding to and preventing access to the BMP receptors. Previous groups have identified that Grem1 can interact with several cell surface receptors including VEGFR2 and heparin sulphate proteoglycans [43,45]. Our data suggest that these cell surface receptor interactions do not "capture" sufficient Grem1 to allow significant inhibition of BMP signalling in HK-2 cells.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…These data also suggest that rhGrem1 is not binding to and preventing access to the BMP receptors. Previous groups have identified that Grem1 can interact with several cell surface receptors including VEGFR2 and heparin sulphate proteoglycans [43,45]. Our data suggest that these cell surface receptor interactions do not "capture" sufficient Grem1 to allow significant inhibition of BMP signalling in HK-2 cells.…”
Section: Discussionmentioning
confidence: 63%
“…Given the critical role of Grem1 posttranslational processing and glycosylation in its function [43], the ability of Grem1 expression to inhibit BMP action when expressed in mammalian cells was then assessed. After optimization, a protocol was developed whereby > 80 % transfection efficiency was routinely obtained in HEK293 cells using pcDNA3.1A containing the human Grem1 cDNA (Fig.…”
Section: Overexpression Of Human Gremlin1 Inhibits Bmp Signalling In mentioning
confidence: 99%
See 1 more Smart Citation
“…Alginate pellets containing 0.1-1.0 pmol per pellet of TR-644 or CA4 were grafted on the chorioallantoic membrane (CAM) of fertilized chicken eggs at day 11 [24]. After 72 h new blood vessels converging toward the implant were counted at 59 magnification under a stereomicroscope.…”
Section: Cam Assay In Fertilized Chicken Eggsmentioning
confidence: 99%
“…14) and VEGFR2-overexpressing GM7373 cells (GM7373-VEGFR2 cells; ref. 31) were incubated with 60 mmol/L KIN59 or vehicle for 30 minutes, after which 10 ng/mL FGF2 or 30 ng/mL VEGF was added. After 10 minutes of stimulation, cells were lysed and 50 mg aliquots of the cell extracts were analyzed by SDS-PAGE followed by Western blotting with anti-P-FGFR1 antibody (Santa Cruz Biotechnology), anti-p-Akt antibody (Cell Signaling Technology), and anti-p-VEGFR2 antibody (R&D Systems).…”
Section: Western Blot Analysismentioning
confidence: 99%